Digital Skills of Educational Administrators - Juinakorn, Phapinwich; Daroonsin, Mungkornkaew; Pansiri, Wannaree (Journal of Multidisciplinary in Humanities and Social Sciences, 2026)
In the digital era, school administrators play a critical role in shaping directions and driving change in educational organizations. A review of the existing literature indicates that most digital skills frameworks tend to describe skills as discrete components or primarily focus on students and teachers, while frameworks that systematically explain digital skill readiness specifically for school administrators remain limited. This gap highlights the need for a conceptual framework that reflects the structural and developmental dimensions of digital skills in educational management. The purpose of this article is to examine the digital skills of school administrators and to develop an integrated conceptual framework through a literature-based synthesis. This study adopts a conceptual approach based on a comprehensive review of relevant literature covering educational management, the digital era, digital skills of school administrators, and change management in education. The synthesis of these perspectives led to the development of the 5D Digital Skills Model, which conceptualizes digital skills as an interconnected system of dimensions that collectively represent administrators’ digital readiness. The proposed 5D Digital Skills Model serves as a conceptual framework for analyzing and designing the development of school administrators at both policy and practical levels. It provides a structured lens for understanding digital skill development in educational leadership and offers guidance for administrator development initiatives in response to ongoing digital transformation in education.